Pigment-Producing Bacteria Isolated from the Sea of Marmara, Türkiye: Isolation, Identification, and Characterization - Tetik, Nurten; Arici, Muhammet; Sel, Sabriye; Altug, Gulsen; Turetken, Pelin Saliha Ciftci (SPRINGER, 2026)
Synthetic dyes are widely used in the textile and food industries and pose significant environmental and health risks. Therefore, interest in sustainable, non-toxic, and biodegradable natural pigments is increasing. Microbial pigments bioactive color compounds synthesized by bacteria, yeast, and algae offer a strong alternative to natural pigment sources due to their rapid production capacity, ability to grow on low-cost substrates, and resistance to environmental conditions. In this study, the pigment production potential of bacteria isolated from the Sea of Marmara was investigated, and the pigments were produced under suitable growth conditions for further characterization. The isolates were identified at the molecular level by 16S rRNA gene sequence analysis. Among a total of 11 pigment-producing bacterial isolates, four isolates (numbered 15, 42, 61, and 63) showing intense pigment production in the medium were selected for detailed analysis. The isolates were assigned to Pseudoalteromonas ulvae, Salinicoccus roseus, Exiguobacterium acetylicum, Tenacibaculum lutimaris, Shewanella oneidensis, Zobellia galactanivorans, and Maribacter dokdonensis. Pigment extraction was performed from these strains using 95% methanol and the characterization of the pigments was as follows; It was done by Thin Layer Chromatography (TLC), Ultraviolet-Visible Spectroscopy (UV-Vis), Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimeter (DSC) and Liquid Chromatography-Quadrupole time of flight Mass Spectrometry (LC-QTOF-MS/MS) methods. Among these isolates, violet colored violacein pigment was produced by Pseudoalteromonas ulvae, whereas riboflavin pigment production was observed in Zobellia galactanivorans and Tenacibaculum lutimari. [GRAPHICS]
Keywords: Bacterial pigments; Natural pigments; Marmara sea; Pigment production; Pigment characterization; VIOLACEIN; FOOD; Microbiology